Thermal And Rheological Properties Of 3D Printed Polylactic Acid Plasticized With Polyethylene Glycol - Nor Ashikin, Nor Fazreeniza (Universiti Sains Malaysia, 2018)
In this work thermal, rheological and morphological properties of Polylactic acid (PLA) with 10 wt% polyethylene glycol (PEG) after melt blended at two different temperatures were investigated. The properties were compared with neat PLA and commercial PLA filament used for 3D printing. PLA/10 wt% PEG blend was prepared using single screw extruder to produce pellet for hot press or filament for 3D printing. The different of processing equipment affect thermal properties differently in which for hot pressed blends indicated insignificant changes of melting temperature (Tm) and crystallization temperature (Tc) while 3D printed blends showed reduction of glass transition temperature (Tg) and Tm in the presence of plasticizer. This study also suggested that the commercial PLA filament has higher crystallinity than the pure PLA used. The melt flow index of the PLA increased suggesting reduction of viscosity with 10w*% PEG or increase of temperature. Rheological properties indicated that storage modulus (G‟), loss modulus (G”) and complex viscosity (η*) decreased in the presence of plasticizer but the η* increased after 3D printing process might be due to layer by layer formation at different directions. Morphology shows that the plasticized PLA becomes more ductile with the addition of PEG. In addition, the layers in 3D printed sample prepared at 190°C were wetted well than samples at 170°C suggesting that 190°C is suitable processing temperature for the plasticized PLA. The water absorption test showed higher percentage of water absorption as PEG was added and for 3D printed samples compared with hot pressed sample.